AB0030 Cytokine Profiles in Systemic Lupus Erythematosus and Rheumatoid Arthritis. (15th July 2016) - Novikov, A.; Aleksandrova, E.; Verizhnikova, Z.; Panafidina, T.; Popkova, T.; Karateev, D.; Luchihina, E.; Nasonov, E.
Abstract : Background: Our aim was to compare serum levels of cytokines in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Objectives: Comparative data on cytokine profile in SLE and rheumatoid arthritis RA patients are scarce. Methods: We examined serum samples from 80 pts with SLE, median and interquartile range (25th–75th percentile) of disease duration 48 (2–432) months; age 31, 5 (16–65) years; 72 female; 74 pts with RA, disease duration 90, 0 (30, 00–192, 0) months; age 54, 0 (44, 0–62, 0) years; 59 female, and 28 healthy donors. Cytokine analyses were performed with Bio-Plex® technology (Human Grp I Cytokine 27-plex panel). Results: Pts with SLE had significantly lower levels of IL-1β, -1ra, -2, -9, eotaxin, G-CSF, IFN-γ, MIP-1β, TNF-α, VEGF and higher levels of IL-4, -6, -8, -12, GM-CSF, MCP-1, PDGF-BB, RANTES than healthy donors. Compared to RA, cytokine/chemokine levels from SLE were significantly different. The concentrations of IL-1β, -1ra, -2, -5, -6, -7, -9, -10, -13, 15, eotaxin, FGF, G-CSF, IFN-γ, IP-10, MIP-1α, TNF-α, VEGF in SLE were significantly lower than RA. The concentrations of IL-4, -8, MCP-1, MIP-1β, PDGF-BB, RANTES was higher in the SLE cohort (Table 1 ). Conclusions: Serum concentration of most proinflammatory, Th-2 related, bone marrow–derived cytokines, stromal cells and angiogenic factors in SLE pts is substantially lower than in healthy donors and pts witch RA. These data demonstrate significantly higher chemokine levels in SLE versus RA. References: Chun HY, Chung JW, Kim HA, Yun JM, Jeon JY, Ye YM, Kim SH, Park HS, Suh CH. Cytokine IL-6 and IL-10 as biomarkers in systemic lupus erythematosus. J Clin Immunol. 2007; 27(5):461–6. Kokkonen H, Söderström I, Rocklöv J, Hallmans G, Lejon K, Rantapää Dahlqvist S. Up-regulation of cytokines and chemokines predates the onset of rheumatoid arthritis. Arthritis Rheum. 2010; 62(2):383–91. doi: 10.1002/art.27186. Sieber J, Daridon C, Fleischer SJ, Fleischer V, Hiepe F, Alexander T, Heine G, Burmester GR, Fillatreau S, Dörner T. Active systemic lupus erythematosus is associated with a reduced cytokine production by B cells in response to TLR9 stimulation. Arthritis Res Ther. 2014;16(6):477. doi: 10.1186/s13075-014-0477-1. Disclosure of Interest: None declared